CREDIT UNION SEBAGAI GERAKAN SOSIAL - William Chang (Jurnal Ledalero, 2014)
As a social movement, Credit Unions (CU) display the social, economic and cultural strength of little people. In line with contemporary developments and the advance of modern technology, the management of CUs needs to be monitored, evaluated and adapted to the social, economic and political situation that is continually changing. Nevertheless, in the midst of change the values of the CU are perennial and are very much needed in the movement. After looking at the founding and development, strengthens and weaknesses of the CU, this essay advances concrete steps for handling them. Kata-kata kunci: CU, gerakan sosial, kesejahteraan, pembudayaan nilai-nilai, keadilan, kearifan, keberanian, kejujuran dan tanggungjawab, tantangan-tantangan CU.